Mathematics on Cirebon Woven Fabric with Lanang Motifs - Ibnu Hasan Bisri; Arif Muchyidin (MASI Mandiri Edukasi, 2022)
This study aims to know the mathematical elements in the lanang motif woven fabric, construct a mathematical model on the increasingly lanang patterned weaving, and construct a new mathematical model for the new lanang motif woven fabric. The data was obtained in the form of qualitative data using interview data collection techniques, observations, documentation and field notes with data analysis, namely domain analysis, taxonomic analysis, component analysis and theme analysis. The results showed that the lanang-patterned woven fabric has geometric shapes, namely pentagons, rhombuses and triangles, to make pentagons, rhombuses and triangles using a pattern formed from small polygons called a rhombus-shaped unit lattice. The mathematical model used in this research is the matrix; to create a pentagon requires a matrix of order 103 × 210, to form a rhombus requires a matrix of order 103 × 338, and to develop a triangle involves a matrix of order 103 × 348. These patterns can create new designs by manipulating the rows contained in the matrix owned by each shape.